Utilização de análise de agrupamento na caracterização do perfil agrícola e climático da região sudeste do Estado de Mato Grosso - Oliveira, José Roberto Temponi de [UNESP]; Padovani, Carlos Roberto [UNESP] (EIA Energy in Agriculture, 2010)
The multivariate analysis grouping was used to characterize the productive and climate profile of southeastern of Mato Grosso state. This technique allowed the junction of similar micro regions from characteristics of productivity and climatic, without the need for the assumption of the number or structure of the groups. Cluster analysis allowed the design of a mosaic of spatial heterogeneity regions. It established different profiles in the composition of groups, joining the more traditional in the culture of a species, or more productive, or those for the development of a particular culture. The results obtained by estimation of the climatic parameters and the multivariate procedures enabled the provision of systematic information that will allow farmers to better decision-making on the competitiveness and maintaining the flow of investment in agricultural sector southeastern Mato Grosso.

Com o objetivo de caracterizar o perfil produtivo e climático do Sudeste do Estado de Mato Grosso segundo microrregiões semelhantes a partir de suas características observadas nas medidas de produtividade e climáticas, quando nenhuma suposição foi feita concernente ao número de grupos ou a estrutura do grupo, utilizou-se a técnica multivariada da análise de agrupamento. A análise de agrupamento permitiu desenhar um mosaico de heterogeneidade espacial e estabelecer diferentes perfis na composição dos grupos de microrregião, reunindo as mais tradicionais, ou mais produtivas, ou aquelas mais propícias ao desenvolvimento de determinada cultura. Os resultados obtidos pelos procedimentos de caracterização da produtividade agrícola e característica climatológica da região, possibilitaram o fornecimento de informações sistematizadas que permitirão aos produtores rurais uma melhor tomada de decisão quanto à competitividade e a manutenção do fluxo de investimentos no setor agrário do sudeste mato grossense.
Use of cluster analysis in the characterization of the profile of agricultural and climatic southeast State of Mato Grosso
Keywords: Agricultural production; Climate change; Multivariate analysis; Produtividade agrícola; Variação climática; Análise de agrupamento